Comparison of Efficacy and Safety of Basal and Premixed Insulin Regimens among Type II Diabetes Patients Transiting From Oral Agents to Insulin - S.A, Sirajudeen; CK, Danapal; NK, Abdulla; DP, Sam; MA, Khalid (Indian Journal of Pharmacy Practice)
Introduction: Achievement and maintenance of tight glycemic control in type II diabetes require insulin when oral hypoglycemic agents fail to achieve target HbA1C. There is a lack of uniform consensus as to which of the regimens should be recommended to initiate insulin treatment in these patients. Objectives: To compare the efficacy and safety of adding basal insulin to oral agents versus switching to twice-daily premixed insulin in type II diabetic patients insufficiently controlled by oral hypoglycemic agents(OHAs). Research design and methods: This was a single-centre,retrospective study comparing glargine+OHA with premixed 70/30 regimen in patients with type II diabetes whose glycemic targets were not achieved with the use of oral hypoglycemic agents. Results: A total of 138 subjects were eligible for this study. At study end, the mean HbA1c value was lower in the premix 70/30 than in glargine+OHA(8.07±0.15vs.8.44±0.17 %, P<0.0001). The HbA1c reduction was greater in the premix 70/30 than glargine+OHA (-2.316±0.25vs. - 2.489±0.24%,respectively;P<0.0001). More premix70/30 treated subjects reached target HbA1c values than glargine treated subjects (HbA1c≤7.0%: 31.4% vs.26.5%. Similarly, FBG decrease was greater with premix70/30 (mean difference -54.68 ±17.93vs -68.57±9.178, P< 0.0001), and more patients reached target FBG≤ 110 mg/dl with premix 70/30 than with glargine+OHA (30% vs25%). Premix 70/30 patients had fewer confirmed hypoglycemic episodes than glargine+OHApatients (14.3% and 20.6% respectively). Conclusion: Based on the results, premixed biphasic 70/30 appears to be more effective than insulin glargine+OHA and a reasonable choice to initiate insulin therapy in insulin-naive subjects with type 2 diabetes that is not optimally controlled on OHA.
Keywords: Diabetes; OHA; retrospective; FBG; HbA1c